2013
DOI: 10.1212/01.wnl.0000437295.97946.a8
|View full text |Cite
|
Sign up to set email alerts
|

An RCT to treat learning impairment in multiple sclerosis

Abstract: This study provides Class I evidence that the mSMT behavioral intervention improves both objective memory and everyday memory in patients with MS over 5 weeks, with treatment effects lasting over a 6-month period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(123 citation statements)
references
References 31 publications
7
111
2
3
Order By: Relevance
“…A double-blind RCT study of Chiaravalloti et al 45 (n=86) is an example of a study on the effects of cognitive retraining in MS. In the study, the intervention group, which received education on context and imagery to facilitate learning (modified Story Memory Technique), was compared to a placebo group performing non-training-specific tasks.…”
Section: Neuropsychological Rehabilitation As a Treatment Optionmentioning
confidence: 99%
“…A double-blind RCT study of Chiaravalloti et al 45 (n=86) is an example of a study on the effects of cognitive retraining in MS. In the study, the intervention group, which received education on context and imagery to facilitate learning (modified Story Memory Technique), was compared to a placebo group performing non-training-specific tasks.…”
Section: Neuropsychological Rehabilitation As a Treatment Optionmentioning
confidence: 99%
“…Recently, intensive cognitive rehabilitation approaches targeting attention/information processing speed, memory and executive function [2][3][4][5] have been shown to have positive effects on cognitive deficits and quality of life in patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the MS study, the treatment group showed improvements in performance on the CVLT slope and prose memory. 12,14 The TBI sample similarly showed improvement on prose memory but did not demonstrate improvements on the CVLT slope. This lack of change on the list-learning task in the TBI sample is thought to be due to the increased executive demands of the CVLT list-learning task, the presence of executive deficits in persons with TBI, and the limited efficacy of cognitive rehabilitation in the presence of executive deficits in persons with TBI as well as other neurological populations.…”
Section: Discussionmentioning
confidence: 93%
“…A detailed description of the mSMT can be found elsewhere. 12,14,15 Briefly, the mSMT consists of 10 sessions during which 2 skills are taught to facilitate new learning-(1) visualization (sessions 1-4) and (2) context formation (sessions 5-8). The final 2 sessions (9 and 10) focus on applying the newly learned technique to daily life.…”
Section: Treatment Protocolmentioning
confidence: 99%
See 1 more Smart Citation